Low doses of amifostine protect from chromosomal inversions in spleen in vivo when administered after an occupationally relevant X-radiation dose. (2nd June 2009) - Hooker, Antony M.; Grdina, David J.; Murley, Jeffrey S.; Blyth, Benjamin J.; Ormsby, Rebecca; Bezak, Eva; Giam, Kar; Sykes, Pamela
Amifostine is a chemical radioprotector known to protect cells from DNA damage and toxicity normally induced by high-dose radiation exposure. Here, we used the sensitive in vivo pKZ1 mouse chromosomal inversion assay to determine the radioprotective effect of different doses of amifostine in the presence and absence of 250 mGy whole-body X-irradiation, the present radiation dose limit for radiation emergency workers. Amifostine was delivered intraperitoneally 3 h after radiation exposure and spleen tissue sections were analysed for inversions three days later. High doses of amifostine alone (100 and 400 mg/kg) protected from spontaneous chromosomal inversions, whereas 10 mg/kg had no effect and 1 mg/kg induced chromosomal inversions above the spontaneous inversion frequency. However, all doses of amifostine protected from chromosomal inversions normally induced by 250 mGy X-radiation, with the highest doses also protecting from spontaneous inversions. The pattern of chromosomal inversion responses observed here with amifostine is remarkably similar to that observed in our previous studies using single low-dose and two-dose whole-body X-radiation. These results indicate that the reductive as well as other cellular endogenous prosurvival mechanisms associated with amifostine radioprotection will likely play a role in low-dose radiation-induced protection.